“LONTO LEOK” SEBAGAI PRAKSIS KATEKESE KONTEKSTUAL GEREJA LOKAL MANGGARAI - Harbur, Agustinus Manfred (CREDENDUM: Jurnal Pendidikan Agama, 2019)
Catechesis as faith educational process is always contextual because faith is essentially involved in the struggle of concrete life. Catechesis of Manggaraian local church must be contextual. A suitable approach for this contextual catehesis is the "lonto leok" model. Catechesis "lonto leok" is the sharing of faith through which people discuss together their problem in the light of Christian faith. Catechesis "lonto leok", existing in-KBG KBG. The emphasis on practical hermeneutic, used in this model until now, can not truly help the people to encounter Christ, the Word of life, personally. Looking ahead, catechesis "lonto leok" should promote hermeneutic paska, that considering life as a mystery, in which people can meet the calling of God to construct the Kingdom of God in the world. In this way catechesis "lonto leok" can guide people to have a solid, independent, and solider faith.